TREAT-TO-TARGET STRATEGY FOR EARLY PSORIATIC ARTHRITIS (PRELIMINARY RESULTS OF THE REMARCА STUDY) - T. V. Korotaeva; E. Yu. Loginova; D. E. Karateev; A. A. Glazkov; E. L. Nasonov (Научно-практическая ревматология)
The aim of a treat-to-target (T2T) strategy is to achieve a remission or minimal disease activity (MDA).Objective: to investigate the efficiency of the T2T strategy for early psoriatic arthritis (ePsA).Subjects and methods. Twenty-three patients (8 men and 15 women) with ePsA, who met the CASPAR criteria (mean age was 39.1±10.6 years; the median duration of ePsA was 7 [4; 24] months and that of psoriasis was 36 [12; 84] months), were examined. At the patient inclusion and then every 3 months, the investigators assessed the activity of ePsA by DAS and DAS28 and that of psoriasis by BSA (%) and PASI and determined erythrocyte sedimentation rate (ESR) (mm/h), C-reactive protein (CRP) level (mg/l), HAQ. All the patients received monotherapy (MoT) with subcutaneous methotrexate (MTX) (methoject) in a dose of 10 mg/week that was increased by 5 mg every 2 weeks until 20–25 mg/week was reached. The number of patients who had achieved remission (DAS <1.6 or DAS28 ≤ 2.4), low disease activity (LDA) (1.6 ≤ DAS <2.4 or 2.4 < DAS28 ≤ 3.6), MDA, and 20%, 50%, and 70% improvements according to the American College of Rheumatology (ACR) criteria. When LDA/MDA or remission was absent at 3 months of treatment, combined therapy (CoT) with MTX and adalimumab 40 mg once two weeks was used.Results. The baseline median DAS was 3.97 [3.07; 4.67]; DAS28 – 4.33 [3.68; 4.73], PASI, 6 [3.1; 9.7]; BSA, 1 [0.5; 3.65]; CRP, 15 [8.6; 25.1] mg/l; ESR, 15 [8.6; 25.1] mm/h; and HAQ, 0.75 [0.63; 1.25]. After 3 months of MoT, remission defined by DAS and DAS28 was in 13/22.7% of the patients; LDA in 21.7/27.3%, and MDA in 26.1%, respectively. ACR 20, 50, and 70 responses were obtained in 65.2, 26.15, and 8.7% of the patients, respectively. There were significant decreases in the level of CRP (to 5.7 [2.3; 10.7] mg/l), HAQ (0.38 [0; 0.87]), BSA (1 [0.3; 2]), and PASI (7.1 [0; 32.5]). ESR remained substantially unchanged (18 [10; 26] ml/h). Four patients with persistent high disease activity were given CoT; 19 patients continued MTX MoT. After 6 months, DAS/DAS28 remission was in 34.8/39.1% of the patients; DAS/DAS28 LDA in 26.1/39.1%; and MDA in 47.8%, respectively. ACR 20, 50, and 70%improvements were seen in 73.9, 60.9, and 47.8% of the patients, respectively. There were significant reductions in the level of CRP (4.9 [0.9; 8.3]), HAQ (0.13 [0; 0.63]), and BSA (0.35 [0; 1.6]). After MTX MoT, DAS/DAS28 remission was observed in 36.8/36.8% of the 19 patients; LDA in 15.8/36.8%; and MDA in 47.4%. ACR 20, 50, and 70 responses were seen in 68.4, 52.6, and 42.1% of the patients receiving MTX MoT and in 100, 100, 75% of the patients (n = 4) having CoT, respectively; MDA was noted in 50% of the cases.Conclusion. The use of the T2T strategy during a 6-month period could provide ACR 70 response and MDA in half of the patients and remission in one third of the patients with ePsA.